A comparative imaging analysis of paraspinal muscles in healthy individuals and patients with chronic low back pain - Hosapatna Mamatha; Kumar Megur Ramakrishna Bhat; Othman Hakum Said; Lokadolalu Chandrachar Prasanna (Translational Research in Anatomy, 2024)
Background: Chronic low back pain (CBP) is a heterogeneous disease that may be caused by intervertebral disc lesions, age-related degenerative lumbar vertebral bodies, nerve compressions at its exit points, age-related weakness of paraspinal muscles, or tendinous and myofascial causes. This study compared the changes in the cross-sectional area (CSA) of the paraspinal muscles between healthy individuals and patients with CBP at the L4 superior endplate level. Methods: Magnetic Resonance (MR) Images of 50 healthy males without a history of back pain and 50 patients with CBP aged 40–60 years were retrospectively evaluated. The CSAs of the bilateral paraspinal muscles viz multifidus, erector spinae, psoas major, and quadratus lumborum were measured in the axial view at the level of the L4 superior endplate. The sagittal view of the MRI images at the L4 superior endplate level was selected to evaluate intervertebral disc (IVD) abnormalities. Further, these images were subjected to the Tissue Quant algorithm to quantify muscle atrophy and fat deposition. Results: Sagittal section images showed diffuse bulges in the IVD of 28 patients with CBP rather than IVD extrusion or protrusion. Decreased multifidus CSA and a marginal increase in CSA of other paraspinal muscles were observed in CBP patients along with significant fat infiltration within the paraspinal muscles. Conclusion: This study demonstrated a bilateral decrease in the CSA of multifidus muscles in patients with CBP compared with healthy individuals. In contrast, a slight increase in CSA was noted in the remaining paraspinal muscles, which may be due to reduced muscle mass and increased interfascicular fatty infiltration. Evaluating the manifestations of each paraspinal muscle and subsequent strengthening of the concerned muscle should be targeted for treating CBP.